1986
DOI: 10.3382/ps.0650288
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Deoxynivalenol (Vomitoxin) on Dietary Preference of White Leghorn Hens ,

Abstract: In two experiments, a total of 108 laying hens were given two-choice preference tests involving diets containing 4-deoxynivalenol (DON) and control diets that contained little (.2 mg DON/kg) or no DON. The DON was from naturally contaminated white winter (.35 and .70 mg/kg; Experiment 1) or spring wheat (1.4 and 4.5 mg/kg) and purified DON (1.4 mg/kg; Experiment 2). Testing lasted 14 to 16 days for each hen, with the position of the separate feed containers that held the control or DON diet being altered daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Eckel et al [1993] reported that low doses of DON mixed in the diet can alter palatability of pelleted feed to rats, resulting in an immediate, but transient decrease in feed intake and increase in rejection of the adulterated pellets. Also, because Hamilton et al [1985Hamilton et al [ , 1986 found that a small proportions of laying hens actually preferred a DONcontaminated diet over a control clean feed, this further suggested that taste may play a role in feed acceptance. Conversely, though, Clark et al [1987] indicated that DON probably does not alter dietary taste at levels lower than 8 ppm fed to rats.…”
Section: Discussionmentioning
confidence: 99%
“…Eckel et al [1993] reported that low doses of DON mixed in the diet can alter palatability of pelleted feed to rats, resulting in an immediate, but transient decrease in feed intake and increase in rejection of the adulterated pellets. Also, because Hamilton et al [1985Hamilton et al [ , 1986 found that a small proportions of laying hens actually preferred a DONcontaminated diet over a control clean feed, this further suggested that taste may play a role in feed acceptance. Conversely, though, Clark et al [1987] indicated that DON probably does not alter dietary taste at levels lower than 8 ppm fed to rats.…”
Section: Discussionmentioning
confidence: 99%
“…The four groups received either a basal diet (BD, Table 5 ; Control), BD supplemented with 0.15 mg/kg AFB 1 + 1.5 mg/kg DON + 0.12 mg/kg OTA (Toxins), BD + Toxins with 0.29% TOXO HP (Trouw Nutrition, Amersfoort, The Netherlands; Toxins + HP), or a BD + Toxins with 0.1% TOXO XL (Trouw Nutrition, Amersfoort, The Netherlands; Toxins + XL). The doses were chosen on the basis of previous reports that showed that dietary consumption of 0.05–0.6 mg/kg AFB 1 , 0.35–4.5 mg/kg DON, or 0.16–0.33 mg/kg OTA alone can induce negative effects in laying hens [ 42 , 43 , 44 , 45 , 46 ]. The AFB 1 , DON and OTA were produced by Aspergillus flavus NRRL-3357, Fusarium graminearum W3008, and Aspergillus ochraceus AS3.3876, respectively, and mixed into the feeds, as described in previous studies [ 41 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, tendency of feed intake decreased were observed as effect of DON supplementing. It is known that poultry are much less sensitive than pigs to DON, since levels as high as 8 ppm in feeds had not been associated with impaired productivity (Hamilton, 1986). Rapidly growing broilers are generally more sensitive than laying hens to feed refusal (Huff et al, 1986).…”
Section: Discusssionmentioning
confidence: 99%